Assessment Of Seed Vigour Deterioration Pattern Based On Physiological And Biochemical Attributes In Paddy (Oryza Sativa L.) During Storage (Applied Biological Research, 2020)
Seven paddy cultivars viz., ‘ADT 38’, ‘ADT(R) 46’, ‘CO 43’, ‘CO(R) 50’,  ‘CR 1009’, ‘IW Ponni’ and ‘Swarna’ were assessed for deterioration  pattern during natural and artificial ageing. Various physiological and  biochemical attributes associated with seed deterioration were studied in  relation to seed vigour. Decline in dehydrogenase, α-amylase, catalase,  peroxidase, superoxide dismutase activities and increase in electrical  conductivity of seed leachate were observed during natural ageing. The  deterioration during artificial ageing (400C temperature and 100% relative  humidity) followed the same pattern but with accelerated rate. The  disintegration of embryo and aleurone layer was also conspicuous in  accelerated aged seeds. These biochemical changes occurring during  ageing are quite well reflected in terms of physiological attributes like loss  of viability and vigour. Among the evaluated paddy cultivars, ‘CR 1009’ proved superior over all the other cultivars in maintaining higher viability  and vigour potential while cv. ‘ADT 38’ and ‘ADT(R) 46’ showed poor  storability.
Keywords: Ageing; antioxidants; germination; seed vigour; storability